Maqāṣid al-Sharī‘ah and Environmental Protection in Indonesian Islamic Legal Discourse - Arka Zeidan Mahardika Putranto (JUSTISIA GLOBAL EDUKASI, 2026)
Environmental degradation has emerged as a critical challenge affecting ecological sustainability, public welfare, and future generations. In response, Islamic legal scholars increasingly employ the framework of Maqāṣid al-Sharī‘ah to address contemporary environmental concerns and develop normative foundations for ecological responsibility. This study explores the role of Maqāṣid al-Sharī‘ah in shaping environmental protection discourse within Indonesian Islamic legal thought. Using a normative and conceptual methodology, the research examines scholarly writings, fatwas, and legal interpretations that connect environmental preservation with the objectives of Islamic law. The findings demonstrate that environmental protection is increasingly understood as an integral component of safeguarding life, property, human dignity, and public welfare. The study reveals that the maqāṣid framework provides a flexible and comprehensive approach for addressing modern environmental challenges that extend beyond traditional legal categories. Furthermore, Indonesian Islamic legal discourse increasingly recognizes environmental sustainability as a collective moral and legal responsibility grounded in Islamic ethical principles. The research argues that Islamic legal modernism enables the reinterpretation of classical legal concepts to respond effectively to contemporary ecological crises. By emphasizing public interest (maṣlaḥah) and intergenerational justice, Maqāṣid al-Sharī‘ah offers a normative foundation for environmental governance and sustainable development. The study concludes that integrating environmental concerns into Islamic legal reasoning strengthens the relevance of Islamic jurisprudence in addressing global sustainability challenges. These findings contribute to the growing body of scholarship on Islamic environmental ethics and the modernization of Islamic legal thought in Indonesia.